Diferentes sistemas de alojamento de frangos de corte e de coleta de ovos em matrizeiros - Rovaris, Ellen (2013)
There were three experiments. The first to evaluate the performance of broilers raised in two housing types: Treatment 1: conventional treatment and 2: dark house. The results showed that broilers reared in dark house had better body weights at 42 days of age, better weight gain, feed intake and feed conversion. Significant reduction in the incidence of chickens’ foot callus reared in conventional system. The second experiment was conducted to evaluate the quality of hatching eggs and chicks that had been hatched in two systems of egg collection (treatment 1:Manual and treatment 2: automatic), the results showed that eggs collected from nests automated had better hatchability results and lower percentages of bacterial and fungal contamination, since the manuals nests had higher utilization rates and lower floor egg hatching on the. The third experiment was conducted to evaluate the hatchability of fertile eggs defective and verify the viability of the same incubation, the eggs with defects were divided in 6 treatments, treatment 1: eggs crooked, treatment 2: small eggs (45 to 47g), treatment 3 : eggs with microcracks, treatment 4: eggs considered low density (1070), Treatment 5: eggs considered ideal for incubation placed in the tray with the pole inverted (air chamber down) and treatment 6: control, eggs considered ideal hatching. The results showed that the control treatment had the highest rates of embryo mortality and reduced hatchability.